Structural studies on manganese superoxide dismutase - Parker, M (1985)
Superoxide dismutases are widely distributed enzymes which catalyse the dismutation of superoxide radicals to dioxygen and hydrogen peroxide and are considered to be an important agent of an organism's defence against oxygen toxicity. The crystallization and low resolution structure determination of manganese superoxide dismutase (E.G. 1.15.1.1) from Bacillus stearothermophiluB is described. The enzyme crystallized in space group P21212 with two monomers per asymmetric unit and cell dimensions of ̲a=72.2Å, ̲b=111.1Å and ̲c=51.1Å. The crystals diffracted to beyond 2Å resolution but were fragile and prone to cell dimension changes. The cell dimension variability was overcome to some extent by crossllnking with glutaraldehyde. An electron density map was calculated to 6Å resolution initially by the method of multiple isomorphous replacement using data obtained from six heavy atom derivatives. The final map was calculated from single isomorphous replacement data using a map modification procedure. The fitting of an alpha carbon model of iron superoxide dismutase into the map suggested the iron and manganese enzymes are structurally related. The position of the metal atoms in the model solved difference Patterson maps calculated from data collected from a manganese-free crystal and from anomalous dispersion data. The latter data were collected using synchrotron radiation tuned close to the manganese absorption edge. The low resolution map and the availability of 2.4Å resolution native data paves the way for higher resolution X-ray studies of the crystals. A detailed analysis of amino acid sequences has been carried out on the various metal-containing superoxide dismutases. The results indicate that the enzymes can be classified according to their metal cofactor. The distribution and homology of the enzyme classes supports the endosymbiotic theory of the origin of cell organelles. The presence of the copper/zinc enzyme in Photobacterium leiognathi is shown to support the case for a eukaryote to prokaryote gene transfer.